2015
DOI: 10.21091/mppa.2015.4042
|View full text |Cite
|
Sign up to set email alerts
|

The Musician as (In)Active Athlete? Exploring the Association Between Physical Activity and Musculoskeletal Complaints in Music Students

Abstract: OBJECTIVE: Musicians are often compared to athletes because of the physical exertion required to play music. The aim of this study was to explore the physical activity level of music students and to study its relationship with musculoskeletal complaints. A second goal was to assess associations between physical activity and pain, quality of life, and disability. METHODS: This cross-sectional study among third- and fourth-year music students used an electronic survey including measures for physical activity (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 0 publications
3
23
0
2
Order By: Relevance
“…Variations in physiological signs of stress, energy expenditure, and cardiac demands have been documented and related to musicians' physical characteristics, instrument type, and the tempo of music performed (Iñesta et al, 2008;Williamon et al, 2013;Vellers et al, 2015;Romero et al, 2016), suggesting that the physical demands of performance are multiple and changeable. Consequently, musicians-who are sometimes referred to as 'athletes of the upper body' (Quarrier, 1993;Baadjou et al, 2015)-could benefit from being physically and mentally fit in order to perform at the highest levels.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in physiological signs of stress, energy expenditure, and cardiac demands have been documented and related to musicians' physical characteristics, instrument type, and the tempo of music performed (Iñesta et al, 2008;Williamon et al, 2013;Vellers et al, 2015;Romero et al, 2016), suggesting that the physical demands of performance are multiple and changeable. Consequently, musicians-who are sometimes referred to as 'athletes of the upper body' (Quarrier, 1993;Baadjou et al, 2015)-could benefit from being physically and mentally fit in order to perform at the highest levels.…”
Section: Introductionmentioning
confidence: 99%
“…The broad conception of pain found in the performing arts medicine literature is reflected in the variety of measures used to study it. For instance, investigations with musicians often rely on validated questionnaires for the general population, such as the Disabilities of the Arm, Shoulder, and Hand (DASH) Questionnaire, which measures upper‐extremity disability and symptoms, the Standardized Nordic Questionnaire, which measures pain location, or the SF‐12, which measure general physical and mental health . Bespoke surveys have also been constructed, and interviews have been used to shed light on experiences of pain within the wider context of professional life .…”
Section: Introductionmentioning
confidence: 99%
“…Some 22 studies also investigated the association between different MSS outcomes. Similar to the extent/severity studies, the majority (86%) of the studies of risk factors reported general symptom outcomes[27,28,30,38,[40][41][42][43][44][45][46][47][48][49][50]53,54,60,64,65,69,71,74,76,[79][80][81][82][83][84][85][86][87][88][91][92][93][95][96][97][106][107][108]110,111,115,116,119,122,125,126,[129][130][131][133][134][135][138][139][140][141][142][154][155]…”
mentioning
confidence: 99%